2009
DOI: 10.1007/s12291-009-0049-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of bone mineral density with biochemical markers in post menopausal women

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Some of the markers of bone turnover are mentioned in Tables 2 and 3. Recently, two studies have shown that BAP and NTx are related to changes in bone density and are predictors of rate of bone loss after menopause [22,23]. In a study published in 2010, the associations between bone formation and resorption, micronutrient intake and BLLs were studied in women between 20 and 86 years who had participated in NHANES 1999-2002.…”
mentioning
confidence: 99%
“…Some of the markers of bone turnover are mentioned in Tables 2 and 3. Recently, two studies have shown that BAP and NTx are related to changes in bone density and are predictors of rate of bone loss after menopause [22,23]. In a study published in 2010, the associations between bone formation and resorption, micronutrient intake and BLLs were studied in women between 20 and 86 years who had participated in NHANES 1999-2002.…”
mentioning
confidence: 99%
“…The quality of life of women after menopause is one of the key health issues today (Agrawal et al, 2009). There are growing evidences for the importance of nutrition in the maintenance of bones and joints health.…”
Section: Resultsmentioning
confidence: 99%
“…High bone turnover rate seems to play an increasing role as a determinant of bone mass with increasing postmenopausal age.As Hydroxy proline forms 16% of bone matrix, the increase in bone turnover after menopause will show increase in urinary excretion of Hydroxy proline which is proved in our study and consistent with other studies. 6,7…”
Section: Discussionmentioning
confidence: 99%